Single-dose psilocybin-assisted therapy in major depressive disorder: a placebo-controlled, double-blind, randomised clinical trial. (February 2023) - von Rotz, Robin; Schindowski, Eva M.; Jungwirth, Johannes; Schuldt, Anna; Rieser, Nathalie M.; Zahoranszky, Katharina; Seifritz, Erich; Nowak, Albina; Nowak, Peter; Jäncke, Lutz; Preller, Katrin H.; Vollenweider, Franz X.
Summary: Background: Psilocybin has been suggested as a novel, rapid-acting treatment for depression. Two consecutive doses have been shown to markedly decrease symptom severity in an open-label setting or when compared to a waiting list group. To date, to our knowledge, no other trial compared a single, moderate dose of psilocybin to a placebo condition. Methods: In this double-blind, randomised clinical trial, 52 participants diagnosed with major depressive disorder and no unstable somatic conditions were allocated to receive either a single, moderate dose (0.215 mg/kg body weight) of psilocybin or placebo in conjunction with psychological support. MADRS and BDI scores were assessed to estimate depression severity, while changes from baseline to 14 days after the intervention were defined as primary endpoints. The trial took place between April 11th, 2019 and October 12th, 2021 at the psychiatric university hospital in Zürich, Switzerland and was registered with clinicaltrials.gov (NCT03715127). Findings: The psilocybin condition showed an absolute decrease in symptom severity of −13.0 points compared to baseline and were significantly larger than those in the placebo condition (95% CI −15.0 to −1.3; Cohens' d  = 0.97; P = 0.0011; MADRS) and −13.2 points (95% CI; −13.4 to −1.3; Cohens' d  = 0.67; P = 0.019; BDI) 14 days after the intervention. 14/26 (54%) participants met the MADRS remission criteria in the psilocybin condition. Interpretation: These results suggest that a single, moderate dose of psilocybin significantly reduces depressive symptoms compared to a placebo condition for at least two weeks. No serious adverse events were recorded. Larger, multi-centric trials with longer follow-up periods are needed to inform further optimisation of this novel treatment paradigm. Funding: The study was funded by the Swiss National Science Foundation, Crowdfunding, the Swiss Neuromatrix Foundation, and the Heffter Research Institute .